If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + 5x + 3) + -1(9x + 5) = 8x + 3 Reorder the terms: (3 + 9x + 5x) + -1(9x + 5) = 8x + 3 Combine like terms: 9x + 5x = 14x (3 + 14x) + -1(9x + 5) = 8x + 3 Remove parenthesis around (3 + 14x) 3 + 14x + -1(9x + 5) = 8x + 3 Reorder the terms: 3 + 14x + -1(5 + 9x) = 8x + 3 3 + 14x + (5 * -1 + 9x * -1) = 8x + 3 3 + 14x + (-5 + -9x) = 8x + 3 Reorder the terms: 3 + -5 + 14x + -9x = 8x + 3 Combine like terms: 3 + -5 = -2 -2 + 14x + -9x = 8x + 3 Combine like terms: 14x + -9x = 5x -2 + 5x = 8x + 3 Reorder the terms: -2 + 5x = 3 + 8x Solving -2 + 5x = 3 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -2 + 5x + -8x = 3 + 8x + -8x Combine like terms: 5x + -8x = -3x -2 + -3x = 3 + 8x + -8x Combine like terms: 8x + -8x = 0 -2 + -3x = 3 + 0 -2 + -3x = 3 Add '2' to each side of the equation. -2 + 2 + -3x = 3 + 2 Combine like terms: -2 + 2 = 0 0 + -3x = 3 + 2 -3x = 3 + 2 Combine like terms: 3 + 2 = 5 -3x = 5 Divide each side by '-3'. x = -1.666666667 Simplifying x = -1.666666667
| (8x+3x-2)-(8x+4)=9 | | -0.5(6b+8)+5b=6(1-b)-2 | | 11-9x=47-16x | | (10x+8x-3)-(10x+7)=30 | | 8+6r-2=9r+11-2r | | 114-5x=22x+15 | | (19t-13)+(-6t+5)= | | 1-10w=81 | | 5(y+7)=-35(y-1)-40 | | 5x-3=(x+7)+3x | | 2x+12=-87-9x | | 106-6x=2x+18 | | (g-9)5= | | -30-6x=10-10x | | 49-4x=7x+16 | | -7x+8=15 | | -(3y+3)-(-2y-8)=1 | | 7(x-2)=-5(x+3)+22 | | 6(3x-5)=3(6x+9) | | 3mp+-mp= | | 15x+14-2x=3x-3 | | 4+16y-3=8y+34-3y | | 7+3m=-26 | | -6x+9=45 | | 24=-4(x-4)+9(x-3) | | m-1-m+3= | | 7s+7s=98 | | 8(y-3)+4(y+1)=28 | | -8.1x=32.4 | | 2(x-17)=-2 | | -9.5x=19.0 | | 6t=-75 |